Poetic justice: challenging the current court typology and its integration into Kliptown - Anavi, Craig Moshe (My University, 2017)
The Judicial system has existed in society since ancient civilization. It resides in our subconscious and plays a part in our decision making process taking the form of a moral conscience. Furthermore, the judicial system is realized spatially through the visualization of the Court. These institutions are located across all our major cities and suburbs often occupying prime territory. The judicial court is a public building which should promote civic pride and identity, however, it is a building type which has become highly restricted and walled off from society. It was once a space of public and community participation. It is an integral institution in a democratic society. It has now become associated with crime and violation of law. It is a space perceived by many to be avoided. Through this research and design report I wish to challenge the current court typology and explore the potential of the judicial court and the significant impact it can have on society as a great public building which promotes civic pride. Themes of identity, jurisprudence, conscience and boundaries are explored to develop a new court type and a precedent for future judicial buildings. The design proposes a Magistrates Court of a multi-disciplinary nature for the city of Kliptown and the greater Soweto. It is a hybrid of program interlaced together in response to the context and the broader network age we find ourselves in.
This document is submitted in partial fulfillment for the degree of Master of Architecture (Professional ) to the Faculty of Engineering and the Built Environment, school of Architecture and planning, University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--South Africa; Courts--South Africa; Courts--South Africa--Designs and plans